2011
DOI: 10.1080/02755947.2011.646456
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Rainbow Trout Size on Response to Rotenone and Antimycin

Abstract: The piscicides rotenone and antimycin are commonly used to eradicate unwanted fish populations. However, the relationships (if present) between their toxicities and fish sizes are unknown and could be especially important when bioassay fish are used to detect piscicide presence and effectiveness. Size-mediated toxicity could lead to either excessive or inadequate piscicide applications if bioassay fish are larger or smaller than the fish being eradicated. The relationships between time to death and weight of r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 14 publications
0
1
0
Order By: Relevance
“…Similar results were reported for several fish species, including largemouth bass Micropterus salmoides and spotted bass Micropterus punctulatus during both laboratory and field exposures (Hester 1959, Rowe-Rowe 1971, Chadderton et al 2003. Brown et al (2011) found a significant but weak correlation between rainbow trout size and time to death for rotenone exposures. Smaller fish appeared to be affected more quickly, but they did not consistently die before the large fish, and less than 21% of the observed variation could be explained by body size.…”
Section: Discussionmentioning
confidence: 87%
“…Similar results were reported for several fish species, including largemouth bass Micropterus salmoides and spotted bass Micropterus punctulatus during both laboratory and field exposures (Hester 1959, Rowe-Rowe 1971, Chadderton et al 2003. Brown et al (2011) found a significant but weak correlation between rainbow trout size and time to death for rotenone exposures. Smaller fish appeared to be affected more quickly, but they did not consistently die before the large fish, and less than 21% of the observed variation could be explained by body size.…”
Section: Discussionmentioning
confidence: 87%
“…Antimycin A is more toxic to bighead and silver carp when delivered as microparticles of a size similar to those targeted by those species during feeding [561] than to native fish species, including bluegill and largemouth bass [561], with toxicity being greater in warmer water [596]. Rainbow trout (Oncorhynchus mykiss), a salmonid fish species with invasive populations outside its native range in western North America, required longer exposure to kill using antimycin A compared to rotenone when exposed to concentrations typically used for eradication [597]. A significant positive relationship was found between rainbow trout size and time of death for both compounds; however, this relationship was limited in its ability to predict death based on size.…”
Section: Effects Of Pesticides On Non-target Organismsmentioning
confidence: 99%